Selecting appropriate fuzzy PID control structure for power electronic applications. Issue 17 (16th April 2019) - Al‐Greer, Maher; Armstrong, Matthew; Pickert, Volker
Abstract : A comprehensive library of Fuzzy Proportional‐Integral‐Derivative (PID) controllers for power electronic systems has recently presented in the literature. In this library, the authors derived a 27 Fuzzy PID structures and many hybrid Fuzzy PID controllers. This paper is an extended research for the aforementioned work. Here and as a study case, a switched mode power converter (SMPC) application is considered showing the procedure for selecting the applicable structure from the derived FPID library. Such systems require robust, and highly dynamic performance, control schemes to facilitate optimum and high efficiency performance, often under a wide and challenging range of operating conditions. Here, a fuzzy PD + I (FPD + I) structure is directly selected from the derived FPID library. Simulation analysis and experimental validation on a DSP (TMS‐320F28335) controlled prototype synchronous DC‐DC buck converter demonstrate the superior dynamic performance and voltage regulation of the selected FPID structure compared to the conventional CPID control scheme.